TrUStAPIS: a trust requirements elicitation method for IoT - Ferraris, Davide; Fernandez-Gago, Carmen (International journal of information security, 2020)
The internet of things (IoT) is an environment of interconnected entities, which are identifiable, usable and controllable via the Internet. Trust is useful for a system such as the IoT as the entities involved would like to know how the other entities they have to interact with are going to perform. When developing an IoT entity, it will be desirable to guarantee trust during its whole life cycle. Trust domain is strongly dependent on other domains such as security and privacy. To consider these domains as a whole and to elicit the right requirements since the first phases of the system development life cycle is a key point when developing an IoT entity. This paper presents a requirements elicitation method focusing on trust plus other domains such as security, privacy and usability that increase the trust level of the IoT entity developed. To help the developers to elicit the requirements, we propose a JavaScript notation object template containing all the key elements that must be taken into consideration. We emphasize on the importance of the concept of traceability. This property permits to connect all the elicited requirements guaranteeing more control on the whole requirements engineering process.